PENGARUH PEMBERIAN EDUKASI ONLINE TERHADAP PENGETAHUAN DAN SIKAP DALAM PENERAPAN PROTOKOL KESEHATAN PADA SISWA SMAN 92 JAKARTA - Fiqih Nur Aida (2021)
Covid-19 cases are becoming a high health problem both in the world and in Indonesia. To overcome this Covid-19 disease is to implement appropriate and consistent health protocols, namely by always washing hands, wearing masks and maintaining distance (3M). In adolescents, this is increasing because they do a lot of outdoor activities and have high mobility. This study aims to determine the effect of providing online education on knowledge and attitudes in the application of health protocols to students of SMAN 92 Jakarta. The method used is a Quasi Experiment design with a one group pretest posttest design. The sampling technique used nonprobability sampling with purposive sampling technique with a total sample of 96 adolescents. Analysis of the data used is univariate analysis and bivariate analysis with Paired T-test. The results of this study indicate that there is an influence on knowledge before and after being given online education (p value = 0.000), and there is an influence on attitude before and after being given online education (p value = 0.000). Adolescents are able to communicate and discuss in order to increase their knowledge and are able to determine attitudes and be responsible for what they do